2010
DOI: 10.1002/srin.200900064
|View full text |Cite
|
Sign up to set email alerts
|

Inclusions Generated during Ingot Casting of Tool Steel

Abstract: An industrial trial study was carried out at Uddeholm Tooling AB, Sweden, to investigate the mechanisms of the formation of inclusions, especially macro inclusions during ingot casting. Strong evidence of reoxidation was observed. Two types of inclusions generated during casting were detected in the ingot. Inclusions of Type C1 originated from mould powder with reoxidation product Al 2 O 3 as a part of it. Inclusions of this type were usually small. The number of Type C1 inclusions increased from the centre of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…[2] In particular, the generation of non-metallic inclusions during casting process through deoxidization in ladle and mold even as interaction between refractory and steel was investigated. [13,21,22] The present paper focusses on the effect of different carbonbonded crucible materials for ingot casting on size and distribution of non-metallic inclusions and their influence on the mechanical behavior of a case-hardening steel 18CrNiMo7-6 (AISI 4317). Thus, the quasi-static, dynamic fracture toughness, and fatigue behavior were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In particular, the generation of non-metallic inclusions during casting process through deoxidization in ladle and mold even as interaction between refractory and steel was investigated. [13,21,22] The present paper focusses on the effect of different carbonbonded crucible materials for ingot casting on size and distribution of non-metallic inclusions and their influence on the mechanical behavior of a case-hardening steel 18CrNiMo7-6 (AISI 4317). Thus, the quasi-static, dynamic fracture toughness, and fatigue behavior were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The increased oxygen content would result in undesired reoxidation. In a previous study, 5 reoxidation during ingot casting is evidently observed. Alumina is formed on the surface of casting power forming micro-inclusions in the ingot.…”
Section: Introductionmentioning
confidence: 64%
“…The decreased contents of oxygen and nitrogen in the final products are strong evidence of improvement. 5,6 Despite of argon protection, entrainment of oxygen into the liquid steel is still noticed. The increased oxygen content would result in undesired reoxidation.…”
Section: Introductionmentioning
confidence: 99%
“…This can well explain the fact that only the casting powder in the range of 10-30 mm is found in the ingot. 5 Eriksson et al have carried out CFD calculation for ingot filling. 15 Based on the fact that the surface deformation is almost flat at a filling height and the average surface velocity, the authors suggest 25u as the best inlet angle.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of the present research group shows that two new types of inclusions are introduced during ingot casting. 5 While the inclusions of the first new type, macro in size, are formed due to reoxidation, the inclusions of second type are generated by entrainment of casting powder. Findings of inclusions originating from the casting powder are also reported by other researchers.…”
Section: Introductionmentioning
confidence: 99%